Assessment of spatiotemporal features and potential sources of atmospheric aerosols over the Tianshan Mountains in arid central Asia. (1st February 2023) - Ge, Yongxiao; Wu, Na; Abuduwaili, Jilili; Issanova, Gulnura
Abstract: Arid central Asia is characterized by a dry climate with little precipitation and frequent dust storms. At the same time, the Tianshan Mountains, a vitally important water resource supply zone and ecological barrier, are located in the heart of arid central Asia. Frequent dust storms in this region endanger snow and ice melting as well as ecological security within the Tianshan Mountains. In the present study, the CALIPSO data and HYSPLIT model were combined to assess the spatiotemporal features and potential sources of aerosols over the North Tianshan (NT), East Tianshan (ET), Central Tianshan in the East (CTE), Central Tianshan in the West (CTW), West Tianshan (WT), and South West Tianshan (SW). Results showed that the atmospheric aerosol subtypes had an apparent spatial variability. Dust and polluted dust were the two most dominant aerosol subtypes with the two accounting for over 76% of detected aerosols. The occurrence frequency of the dust within NT, ET, CTE, and CTW showed seasonal variation with two peaks in spring and autumn, while that of WT and SW peaked only in summer. The occurrence frequency of polluted dust in the ET region differed from that found in NT, CTE, CTW, WT, and SW. During all seasons, polluted dust was the dominant aerosol subtype recorded at heights from 2 km to 5 km in NT and WT. Vertically, dust and polluted dust were the most common subtypes observed between 1 and 8 km in SW. The top altitude of the dust and polluted dust layer over most of the Tianshan Mountains was greater than 5 km. The thickest dust layer over the Tianshan Mountains appeared in summer with a value larger than 2.0 km, and the thickness of the polluted dust layer was approximately between 1.0 and 1.5 km in spring. In comparison, the southwesterly transport pathways are the primary route for atmospheric aerosols to the Tianshan Mountains, which have the greater potential to carry natural and anthropogenic aerosols. Therefore, the Karakum Desert, Kyzylkun Desert, Moyunkum Desert, and Gurbantunggut Desert are the primary potential sources of dust and polluted dust aerosols over the Tianshan Mountains in arid central Asia. Highlights: Dust and polluted dust are the two most dominant aerosol subtypes over Tianshan Mountains. The thickest dust layer appeared in summer with a value larger than 2.0 km, and the thickness of the polluted dust layer was approximately between 1.0 and 1.5 km in spring. The southwesterly pathways are the primary route for atmospheric aerosols to the Tianshan Mountains.